"You Can't Ignore a Number This Big": Gender, Risk, and Responsibility in Online Advocacy for Women's Brain Health. (March 2021) - Mohr, Victoria; Kleinherenbrink, Annelies; Varis, Piia
Alzheimer's disease affects more women than men and has therefore been highlighted as a women's issue. However, there is much debate regarding the nature of this gap, with some studies pointing to sex/gender differences in longevity to explain the disparity. Against this background of empirical uncertainty, we ask how online women's brain health campaigns position women as specifically at risk of developing the disease. Using a multimodal approach, we examine how these platforms relate womanhood to risk, prevention, and responsibility. Four main themes emerged: risk quantification, risk management, risk dispersion, and the gendering of risk. We confirm previous studies that identified a dual discourse in which Alzheimer's is represented as both a catastrophic threat and as a fate that individuals can and must prevent. We find that both constructions are intensified on women-oriented platforms compared with nonspecific websites. Ethical implications of the individualization and gendering of risk and responsibility are discussed.